Taxation and corporate finance in Ghana: how do they affect environmental quality? - Paul Adjei Kwakwa (Cogent Business & Management, 2024)
Countries have greatly depended on taxes and corporate finance to support government expenditures and business activities, respectively. However, contrasting arguments on their effects on environmental quality prevail in literature. While Ghana's carbon dioxide emissions have seen an upward trend with taxes and corporate finance, their role in the level of carbon emissions is uncertain. This paper assesses the effect of tax and corporate finance on Ghana's carbon dioxide emissions. Time-series data from 1971 to 2021 from the World Bank were used for analysis. The Autoregressive Distributed Lag (ARDL) estimation technique shows that in the short run, tax positively affects carbon dioxide emission, while trade openness and government expenditure reduce it. In the long run, tax and corporate finance increase carbon emissions. However, urbanization, trade openness and government expenditure reduce carbon emissions. Policy wise, financial institutions should be motivated to set aside special funds to support green activities. In addition, restructuring Ghana's tax system to have an explicit environmental tax meant to reduce carbon emissions is needed. Committing significant portions of tax revenues to support research and development towards energy efficiency is necessary to attain low carbon economy.
Keywords: 650; Taxation; corporate finance; environmental quality; sustainable development; carbon dioxide emissions